Effectiveness of Psychological First Aid and Communication Skills in Enhancing Self-Efficacy: A Randomized Controlled Trial - Rahmi, Alfiatur; Marlina; Marthoenis (Queeva Publishing, 2025)
Background: Supporting students' psychological well-being is crucial for teachers, particularly in times of crisis. However, communication barriers and low confidence in administering Psychological First Aid (PFA) often hinder effective support. This study examines the impact of PFA training and interpersonal communication skills on educators' self-efficacy. Methods: A randomized controlled trial with cluster sampling was conducted among 88 educators from four schools in Aceh (September–October 2024). Participants were assigned to intervention and control groups, with data collected using a pre-test and post-test design. The intervention consisted of PFA and interpersonal communication training, delivered in 2-hour sessions over four weeks. Self-efficacy was measured using the General Self-Efficacy Scale, with data analyzed using normality tests, the Wilcoxon Signed-Rank Test, and the Mann-Whitney U Test. Results: Educators who received PFA training showed significantly higher self-efficacy compared to the control group (U = 537.500, p < 0.001; Wilcoxon Z = -5.785, p = 0.001). Similarly, interpersonal communication training led to significant self-efficacy improvements (U = 306.500, p = 0.001; Wilcoxon Z = -5.783, p < 0.001). Conclusion: PFA and interpersonal communication training enhance teachers' self-efficacy in providing psychological support. Wider implementation of these interventions is recommended to improve students' psychological well-being in Aceh.